Nano Carbon Tracing-based Treatment of Breast Cancer Lymphadenectomy and Nursing Intervention of Postoperative Lymphedema - Li, Xiaonan; Fu, Haimei; Li, Panpan; Li, Yang; Li, Wanyang; Zhu, Fudi (Cellular and Molecular Biology, 2022)
Abstract: to investigate the tracing and therapeutic effects of carbon nanoparticles epirubicin (CNP-EPI) on axillary lymphadenectomy for breast cancer and postoperative lymphedema nursing intervention, a total of 60 breast cancer patients in Harbin Medical University Cancer Hospital were selected as the study subjects and randomly divided into group A (n=30) and group B (n=30). They were subcutaneously injected with 1 mL of CNP-EPI 1 day before surgery and 3 days before surgery, respectively, and underwent axillary lymph node dissection. Lymphedema nursing intervention and routine care were implemented in groups A and B, respectively. After adsorption of 2 mL of 6 mg/mL epirubicin by 1 mL carbon nanoparticles, epirubicin could be slowly released with a cumulative release rate of 64.7 %. The black staining rate was 80.2 % (341/425) in group A and 57.7 % (217/376) in group B, and the difference was statistically significant (P < 0.05). The black staining rate in metastatic lymph nodes was 73.1 % (23/52) in group A and 65.9 % (27/41) in group B (P > 0.05). The incidence rate of edema at 1, 3, and 6 months after operation in group A was significantly lower than that in group B (P < 0.05). Carbon nanoparticles have strong adsorption properties and slow drug release ability; subcutaneous injection of CNP-EPI axillary lymph nodes around the areola 1 day before surgery has a better lymphatic tracing effect; lymphedema nursing intervention can effectively reduce the incidence of prognostic lymphedema.